Male flowers reveal the true identity of a new species of Hechtia (Bromeliaceae) from the Mexican state of Jalisco - Ramírez-Morillo, Ivón; Ramírez-Díaz, Claudia J.; Brunel, Juan Pablo Ortiz; Romero-Soler, Katya J. (Phytotaxa, 2023)
A new species of Hechtia (Bromeliaceae, Hechtioideae) from the Mexican state of Jalisco and from the Pacific Lowlands biogeographical province is proposed as Hechtia carrilloi. Herbarium specimens of this new species were initially assigned to Hechtia santanae but after the study of living plants and fresh male flowers, we concluded that they differ in several features, including leaf surface (sparsely lepidote to glabrous vs. densely lepidote), flower size (4–5 mm long, 1–2 mm in diameter vs. 5–5.5 mm long, 3.8–4.2 mm in diameter), corolla shape (tubular vs. obconical), and anther color (maroon vs. reddish). A complete description based on female and male plants as well as fruits is provided. Likewise, photographs and illustrations showing diagnostic characters and habitat features are included. Additionally, an assessment of the conservation status of the new taxon based on the B criteria of the IUCN is presented.